Implementing effective eLearning for scaling up global capacity building: findings from the malnutrition elearning course evaluation in Ghana. Issue 1 (31st December 2020) - Annan, Reginald Adjetey; Aduku, Linda Nana Esi; Kyei-Boateng, Samuel; Yuen, Ho Ming; Pickup, Trevor; Pulman, Andy; Monroy-Valle, Michele; Ashworth, Ann; Jackson, Alan A.; Choi, Sunhea
ABSTRACT: Background: Global demand for capacity building has increased interest for eLearning. As eLearning resources become more common, effective implementation is required to scale up utilization in Low- and Middle-Income Countries (LMICs). Objective: This paper describes the process of implementing a malnutrition eLearning course, effectiveness of course delivery models devised, factors affecting course completion, and cost comparison between the models and face-to-face training at healthcare and academic institutions in Ghana. Methods: Four delivery models: Mobile Training Centre (MTC), Online Delivery (OD), Institutional Computer Workstation (ICW) and Mixed Delivery (MD) – a combination of OD and ICW – were determined. Participants were enabled to access the course using one of the four models where contextually appropriate. Pre and post-assessments and questionnaires were administered to compare participants' course completion status and knowledge gain between delivery models. The effect of access to computer and Internet at home and relevance of course to job and academic progression on course completion were further investigated. Comparison of delivery model costs against face-to-face training was also undertaken. Results: Of 7 academic and 9 healthcare institutions involving 915 people, 9 used MTC (34.8%), 3 OD (18.8%), 3 ICW (34.2%) and 1 MD (12.2%). Course completion was higher among institutions where the course was relevant to job or implemented as part of required curriculum activities. Knowledge gain was significant among most participants, but higher among those who found the course relevant to job or academic progression. The implementation costs per participant for training with MTC were £51.0, OD £2.2, ICW £1.2 and MD £1.1, compared with a face-to-face training estimate of £105.0 (1 GHS = 0.14 GBP). Conclusion: The malnutrition eLearning course makes global capacity building in malnutrition management achievable. Adopting contextually appropriate delivery models and ensuring training is relevant to job/academic progression can enhance eLearning effectiveness in LMICs.